Implementasi Pembiasaan Sholat Berjama'ah sebagai Pendidikan Karakter bagi Peserta Didik Madrasah Ibtidaiyah - Nurul Syifa; Fahmul Hikam Al-Ghifari (AL-THIFL : Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to analyze the implementation of congregational prayer habituation as a character education effort for students at Madrasah Ibtidaiyah. The scope covers the implementation process, challenges, and impact of congregational prayer habituation on the formation of Islamic character values and attitudes. The method employed is qualitative research using observation, interviews, and documentation techniques at Madrasah Ibtidaiyah. The findings indicate that consistent habituation of congregational prayer effectively enhances discipline, active worship participation, positive social interactions among students, and strengthens the internalization of Islamic character values in daily life. Initial resistance from students and limited supporting resources were identified as challenges. In conclusion, congregational prayer habituation serves as an effective character education strategy and can be a sustainable model for student development in madrasah settings.